Those Inventive Americans - Amrine M.; Battison E. A.; Binns J. J.; Bruce R. V.; Douglas P.; Evett R.; Allen W. L.; Carmichael L. (Washington, D.C. National Geographic Society, 1971)
"The stories of America's inventors abound in genius, insight, and ambition - along with frustration and heartbreak. But they also tell much more: With 242 illustrations, they sketch the development of a Nation." - from the book jacket.
Keywords: 001.894